2017
DOI: 10.1111/obr.12590
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to increase the efficacy of using gut microbiota for the modulation of obesity

Abstract: Obesity is one of the most serious global public health challenges of the 21st century. The adjustment of gut microbiota is often recommended as an efficient strategy to treat obesity. This modulation of gut microbiota can be performed by many methods, including dietary intervention, antibiotic application, the use of prebiotics and probiotics, bariatric surgery and faecal microbiota transplantation. In most cases, positive effects have been observed in response to treatment, but invalid and even contrary effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 163 publications
(216 reference statements)
0
23
0
Order By: Relevance
“…Emerging evidence supports the benefits of a favorable profile of GM in weight management . Many natural products, including plant foods and phytochemicals, have been found to be effective in weight management by modulating GM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence supports the benefits of a favorable profile of GM in weight management . Many natural products, including plant foods and phytochemicals, have been found to be effective in weight management by modulating GM .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports the benefits of a favorable profile of GM in weight management . Many natural products, including plant foods and phytochemicals, have been found to be effective in weight management by modulating GM . However, there has been a lack of conclusive data on the specific phylum(s) of microbiota that was responsible for the anti‐obesity effect observed in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that lipopolysaccharide (LPS), which is produced by Gram‐negative bacteria, can penetrate the intestinal barrier to enter the blood circulation and induce intestinal endotoxemia . Nevertheless, the mechanism by which the gut microbiota regulate the host's energy metabolism is unclear . Intestinal endotoxemia is a critical factor in obesity and metabolic abnormalities, and the intestinal barrier plays an important role in these processes …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Nevertheless, the mechanism by which the gut microbiota regulate the host's energy metabolism is unclear. 8 Intestinal endotoxemia is a critical factor in obesity and metabolic abnormalities, and the intestinal barrier plays an important role in these processes. 9 Plasma endotoxin levels decrease postoperatively in some patients after RYGB.…”
Section: Introductionmentioning
confidence: 99%
“…Among factors, intestinal microbiota can influence the whole-body metabolism by affecting the host's energy homeostasis (de Vadder & Mithieux 2018;Omari-Siaw et al 2016). There are ample studies showing that probiotics and prebiotics, or other dietary substances, can be used to alleviate obesity through the modulation of the host's intestinal microbiota (Bird et al 2017;Li et al 2017a;Li et al 2017b). However, to date, the role of intestinal microbiota in the formation and progression of obesity has not been systematically presented using bibliometric analysis.…”
Section: Introductionmentioning
confidence: 99%